Kinerja Keuangan Bank Umum Syariah: Perbandingan Malaysia, Arab Saudi, dan Indonesia - Dhifta Himmah Yasya; Abdullah Fauzan (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
This study aims to compare the financial performance of Islamic banks in the top three countries according to the Global Islamic Economic Indicator (GIEI), namely Malaysia, Saudi Arabia, and Indonesia. This study employs a quantitative approach using the CAMEL framework, this study improves bank performance in terms of capital adequacy ratio (CAR), profitability (Return on Assets/ROA), and asset quality (Non-Performing Financing/NPF). The results showed that Bank Muamalat Indonesia has the highest CAR ratio, reflecting good capitalization capabilities. Meanwhile, Al-Rajhi Bank from Saudi Arabia showed the best performance in terms of profitability with an excellent ROA. Maybank Islamic Berhad from Malaysia, despite its consistent performance, shows a higher NPF value, signaling greater risk in financing. This research provides valuable insights for the development of Islamic banking in developing countries. In addition, the study also identifies various challenges and opportunities that each bank faces in an effort to improve their financial performance.